Maternal socioeconomic factors and the risk of premature birth and low birth weight in Cyprus: a case–control study - Stylianou-Riga, Paraskevi (Reprod Health, 2018)
BACKGROUND: Prematurity and low birth weight are significant predictors of perinatal morbidity and mortality and are influenced by the overall health and socioeconomic status of the pregnant mother. Although Cyprus is characterized by the highest prematurity rate in Europe (13.1% in 2014), the relationship between maternal health and socioeconomic characteristics with prematurity and low birth weight has never been investigated. We aimed to investigate the association of maternal demographic, clinical and socioeconomic characteristics with premature delivery and low neonatal birth weight in Cyprus. METHODS: In a case-control design, questionnaire data were collected from 348 women who gave birth prematurely (cases) and 349 women who gave birth at term (controls). Information was obtained on gestation duration and birth weight as well as maternal demographic, socioeconomic and clinical profiles, including parameters such as smoking, body mass index, alcohol consumption, presence of gestational diabetes and mental health factors. RESULTS: Premature delivery was associated with greater maternal age (OR: 1.12, 95% CI: 1.06–1.18), absence of gestational diabetes (OR: 0.53, 95% CI: 0.30–0.97), long working hours (OR: 3.77, 95% CI: 2.08–6.84) and emotional stress (OR: 8.5, 95% CI: 3.03–23.89). Within the cases group, emotional stress was also associated with lower birth-weight (β: -323.68 (95% CI: -570.36, − 77.00). CONCLUSIONS: The findings of this study demonstrate the positive association of maternal psychological factors, working conditions as well as maternal age with prematurity and low birth weight in Cyprus. Additional, prospective, studies are needed in the country to further investigate these associations and inform public health intervention measures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12978-018-0603-7) contains supplementary material, which is available to authorized users.